2019
DOI: 10.1111/cea.13393
|View full text |Cite
|
Sign up to set email alerts
|

Maternal IgG impairs the maturation of offspring intrathymic IL‐17‐producing γδT cells: Implications for murine and human allergies

Abstract: Background The precise mechanism involved in the acquisition of the IL‐17+ profile of γδT cells, the ligands responsible for this change, and whether this default is acquired during intrathymic maturation need to be elucidated. Objective This study aimed to evaluate whether IL‐17‐producing γδT cells are present in the airways of tolerant offspring from allergen‐sensitized mothers and the possible implication of maternal IgG in the generation of these cells. Methods Female mice were immunized or not, and the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 50 publications
3
32
0
Order By: Relevance
“…Next, we performed an in vivo experiment in which both purified IgG pools were passively transferred to females during pregnancy at a dose that was determined based on previous experiments by our group [ 26 , 28 ]. This experiment revealed that the passive transfer of OVA-IgG induced a higher frequency of total B cells (including ProB, PreB, and MatB cells) expressing CD1d at a high intensity but a reduced frequency of mature B10 cells (CD5 + IL-10 + CD1d high ) in the offspring thymus ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Next, we performed an in vivo experiment in which both purified IgG pools were passively transferred to females during pregnancy at a dose that was determined based on previous experiments by our group [ 26 , 28 ]. This experiment revealed that the passive transfer of OVA-IgG induced a higher frequency of total B cells (including ProB, PreB, and MatB cells) expressing CD1d at a high intensity but a reduced frequency of mature B10 cells (CD5 + IL-10 + CD1d high ) in the offspring thymus ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…Extensive literature evidence demonstrates that the immune status of IgG donors may be related to differential modulation of thymic lymphocytes [ 26 , 31 , 45 , 46 ], which has been discussed in the literature since 2014 [ 6 , 47 ]. Among related observations, nonatopic IgG may be related to thymic maturation of lymphocytes with an allergy inhibition-related cytokine profile induced by γδT cells [ 48 ] as well as T CD4+ and CD8+ cells [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group had been discussing and demonstrating that IgG antibodies can exert a pivotal role mediating the modulation of lymphocytes cytokine production . In this context, we also demonstrated that IgG purified from atopic dermatitis (AD) patients can favor the production of IL‐17 and IL‐10 by thymic TCD4 and TCD8 cells .…”
Section: Introductionmentioning
confidence: 93%